PENGARUH PADAT TEBAR BENIH IKAN GURAME (Osphronemus gouramy) PADA SISTEM TRANSPORTASI TERTUTUP DENGAN PEMBERIAN ANESTESI MINYAK CENGKEH - Iyeda, Chandra; Komariyah, Siti; Febri, Suri Purnama; Khairi, Ikhsanul; SPF (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
This study aims to evaluate the survival rate and oxygen consumption level of gourami fry with different stocking densities. The method used in this study was an experimental method with 4 treatments repeated 3 times. Each treatment was given a clove oil anesthetic dose of 0.05 ml/L. Treatment P1=20 head/L, P2=25 head/L, P3=30 head/L, and P4=35 head/L. The results of this treatment have a significant effect on the survival of gourami seeds and the level of oxygen consumption of gourami seeds. The highest survival rate for gourami fish seeds was in the P4=35 fish/L treatment with a value of 76%, then continued with the P3=30 fish/L treatment with a total value of 73%, and the P1=20 fish/L treatment with a total value of 48%. Meanwhile, P2=25 fish/L obtained the lowest survival value, namely 44%. The highest level of oxygen consumption (TKO) was obtained in the P4=35 head/L treatment, namely 1.13, while the lowest value was obtained in the P2=25 head/L treatment with a total value of 0.77. Based on the results of the research that has been carried out, it can be concluded that the best stocking density for gourami fish seeds with closed wet transportation treatment given clove oil anesthesia is 35 fish/L because it obtains a high survival value.